Kebijakan Dividen dari Perspektive Agency Cost Model (Studi Kasus Perusahaan yang Terdaftar di Bursa Efek Indonesia periode 2011-2013) - Hitten, Akhmad (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
The paper examines the influence of agency theory on dividend policies with free cash flow,maturity, capital structure, and ownership dividend variables. The sample used in this research isIndonesian listed companies with observation period from 2010 to 2013, and the data collectiontechnique used is data pooling or merging data. The data is analyzed with multiple linearregression analysis in SPSS program. The result of this study indicates that free cash flow,maturity, and ownership structure do not influence devidend policies, however capital structureinfluences dividend policies in Indonesian listed companies. The research also implies thatagency cost theory, as the main model of relevance dividend preposition, cannot explaindividend policies in Indonesian Companies. The investors cannot rely solely on dividend policiesin term of investment decisions in the future.